Mucoepidermoid carcinoma mimicking a soft tissue sarcoma: a case report - Sandhu, S.S.; Singh, V.A.; George, J. (2007)
We describe a case that initially presented to the oncology unit as what seemed like a soft tissue sarcoma arising from the thigh. Biopsy of this mass showed that it was a mucoepidermoid carcinoma. This is a very rare presentation of a non-salivary gland primary mucoepidermoid carcinoma.